Soil solution sampling for organic acids in rice paddy soils - Angeles, Olivyn R.; Johnson, Sarah E.; Buresh, Roland J. (Wiley, 2006)
Low molecular weight organic acids (OA), which are intermediates in the anaerobic decomposition of straw incorporated into submerged soils, have been implicated in causing toxicity to young rice (Oryza sativa L.) seedlings. The objective of this study was to develop a method for measuring OA in soil solution in field and greenhouse studies. Three methods of soil solution sampling were evaluated: zero‐tension displacement (ZTD), variable‐tension centrifugation (CFG), and medium‐tension suction sampling through porous tubes (PT). All solution samples were analyzed for OA by high performance liquid chromatography (HPLC) using an ion exclusion column. Use of cation exchange membrane resin strips during sample collection to sorb interfering cations improved OA recovery. Comparison between sampling methods of the OA concentration in soil solution extracted from soil amended with reagent OA was as follows: PT = CFG >> ZTD. Variables between methods that could cause artifacts in OA measurement were tested systematically: solution pH after sampling, headspace gas pressure during sampling, and sorption to sand or soil layers. No artifact effects were observed, and it was concluded that the tension methods sampled a different fraction of soil solution than the zero‐tension method. Since the tension methods extracted a higher concentration of OA, they are recommended for studies comparing treatment effects on OA production. However, it was beyond the scope of this study to determine which soil solution fraction is more relevant to OA toxicity studies with rice seedlings. Between the two tension methods, PT was more convenient for repeated sampling from the same location compared to the destructive nature of centrifugation.